Cancer immunotherapy: current progress and applications - Leong, Pooi Pooi; Seow, Heng Fong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2006)
Cancer immunotherapy is a form of treatment protocol for cancer patients that have been studied intensively over the last two decades. The undesirable side effects during the course of conventional treatment have lead to the development of immunotherapy as an alternative treatment modality. This approach encompasses the use of three different strategies with various immunotherapeutic modalities including (i) cytokines and monoclonal antibodies; (ii) activation of antigen presentation cells (APC) by using antigen-specific peptides or sources of antigens such as tumour lysate; and finally (iii) adoptive transfer of ex vivo activated autologous cytotoxic T-cells. Due to specific-targeting by antigen-specific monoclonal antibodies, dendritic cells and activated CD8 + T-cells, immunotherapy can eliminate tumour cells efficiently but the normal tissues are unaffected. Despite years of investigation, the outcome of immunotherapy-based clinical trials are inconsistent with very low response rates from patients. Several mechanisms have been proposed to contribute to this failure including the presence of regulatory T-cells (Treg), immunomodulatory cytokines, and aberrant gene expression in tumour cells. This review summarises information from about 140 articles and review papers. In addition, it also provides an update on recent trends in combinational immunotherapy with conventional therapy and encouraging results have been obtained. Re- evaluation of previous studies is necessary to fine-tune the design and approach of immunotherapy to ensure better treatment outcomes.